Circulating fatty acids as biomarkers of dairy fat intake: data from the lifelines biobank and cohort study. (19th May 2019) - Pranger, Ilse G.; Corpeleijn, Eva; Muskiet, Frits A. J.; Kema, Ido P.; Singh-Povel, Cécile; Bakker, Stephan J. L.
Abstract: Background: C14:0, C15:0, C17:0 and trans-C16:1( n -7) are often used as biomarkers for dairy fat intake. Trans-C18:1( n -7) and CLA, two fatty acids which are also present in dairy, have hardly been explored. We investigated whether trans-C18:1( n -7) and CLA can enrich the existing biomarker portfolio. Methods: Data were obtained from Lifelines ( n  = 769). Dairy fat intake was determined by FFQ. Fatty acids were measured in fasting plasma triglycerides (TG), phospholipids (PL) and cholesterol esters (CE). Results: Median (25th–75th percentile) intakes of dairy and dairy fat were 322(209–447) and 12.3(8.4–17.4) g/d respectively. A pilot study showed that trans-C18:1( n -7) and CLA were only detectable in TG and PL. Of the established markers, TG C15:0 was most strongly associated with dairy fat intake (standardized β (std.β) = 0.286, R 2  = 0.111). Of the less established markers, TG trans-C18:1( n -7) was most strongly associated with dairy fat intake (Std.β = 0.292, R 2  = 0.115), followed by PL CLA (Std.β = 0.272, R 2  = 0.103) and PL trans-C18:1( n -7) (Std.β = 0.269, R 2  = 0.099). In TG, a combination of C15:0 and trans-C18:1( n -7) performed best ( R 2  = 0.128). In PL, a combination of C14:0, C15:0, trans-C18:1( n -7) and CLA performed best ( R 2  = 0.143). Conclusion: Trans-C18:1( n -7) and CLA can be used as biomarkers of dairy fat intake. Additionally, combining established with less established markers allowed even stronger predictions for dairy fat intake.